Agroforestry systems and their effects on the dynamics of solar radiation and soybean yield - Sgarbossa, Jaqueline; Schwerz, Felipe; Elli, Elvis Felipe; Tibolla, Liliane Bárbara; Schmidt, Denise; Caron, Braulio Otomar (Comunicata Scientiae, 2018)
Agroforestry systems have been highlighted in the agricultural environment as an alternative form of sustainable production to meet the growing demand for food and energy with less environmental impact. Thus, the aim of this study was to evaluate the effect of different forest species on the dynamics of solar radiation and the productive response of soybean grown in agroforestry systems. Two field experiments were carried out in the city of Frederico Westphalen - Rio Grande do Sul, Brazil. In order to reach the aim of this study, the solar radiation transmissivity and the productive performance of soybean were evaluated. Productivity followed the same tendency as solar radiation transmissivity; in an agricultural year, the species with the higher incidence of solar radiation to the understory presented the best yield. The forest species Schizolobium parayba, Peltophorum dubium and Parapiptadenia rigida were used as they present the potential to compose the agroforestry systems; their canopy structure and leaf architecture provide greater availability of solar radiation in the subforest. The interception of solar radiation by the forest component of more than 50% significantly reduces soybean yield in agroforestry systems, requiring silvicultural practices that promote the availability of solar radiation in the understory.